Wavelet Coherence as a Tool for Considering the Spatial Component of the Banking Activities Description - Vasiurenko, O.; Lyashenko, V. (International Journal of Academic Accounting, Finance & Management Research, 2021)
Banking activity, as a result of the functioning of the banking system, is one of the key directions in a market economy. Banking activities contribute to the attraction and redistribution of free financial resources between various participants in market relations. At the same time, the banking system is able to create conditions for the formation and accumulation of savings by the population. For the implementation of various areas of banking, both classical financial instrume nts and new mechanisms and approaches are used. The main (central) bank of the country provides the basis for the implementation of such directions, the possibility of using such various mechanisms and instruments for the implementation of various areas of banking activity. Control over the conduct of banking activities and, if necessary, appropriate regulation of such activities is also provided by the main (central) bank of the country. For this, various standards and indicators of the functioning of the banking system, individual banks, and areas of banking are considered. The analysis of such indicators and standards is a source of data for making appropriate decisions in the field of banking regulation. We are considering the possibility and feasibility of using the wavelet ideology for this type of analysis. We use the method of estimating wavelet coherence as a key tool for such an ideology. In this case, the object of research is a set of data for many different banks for a certain current date. This makes it possible to talk about the consideration of the spatial component of the description of banking activities. Using real data as an example, the paper presents various estimates of the wavelet coherence of the spatial component of the description of banking activities. Research results are presented in the form of graphs and diagrams. It is shown that the considered approach allows a deeper study of the relationships between the data that we are researching.
Keywords: banking system; wavelet coherence